RANCANG BANGUN MODIFIKASI PAD EYE PADA GALANGAN - Maulana Muslim Dianto; Budi Prasojo; Subagio Soim (Politeknik Perkapalan Negeri Surabaya, 2023)
The function of the pad eye provides a point where the pulley can be hooked directly accordingto the design. The pad eye is installed by welding on the desired area. In the process of installing the padeye, there are obstacles experienced, for example in the installation of the pad eye which takes time dueto the improper welding and welding process. The pad eye modification was carried out to make it easierto do the installation quickly. The pad eye modification has a clamp that can be adjusted in widthaccording to the support. The first step of this pad eye modification is modeling to find out the appropriatedesign on the support, after which material selection is carried out. Followed by the calculation ofallowable stress, tensile and shear. After the calculation results meet the safety criteria, proceed withtesting the pad eye modification using a load cell. The calculation obtained is the largest tensile stress of18.387 MPa, the largest shear stress of 45.969 MPa of the two stresses compared to the permit stress of72 MPa, so it can meet the safety criteria. The bolt strength value is 7.661 MPa from these resultscompared to the permit voltage of 60 MPa. The calculation results show that the pad eye modificationconstruction meets the safety criteria. In strength testing, it is concluded that the pad eye modification isable to lift loads from 500kg to 1500kg.